Influence of starter culture on total free aminoacids concentration during ripening of Krk cheese - Biljana Radeljević; Nataša Mikulec; Neven Antunac; Zvonimir Prpić; Mirjana Maletić; Jasmina Havranek (Mljekarstvo)
The aim of this study was to determine the influence of microbial (commercial starter) culture on concentration of total free amino groups (amino acids) in cheeses in different ripening stages. Free amino groups were determined by reaction with ninhydrin with cadmium (Cd) in the water soluble cheese extract, and were expressed as the concentration of leucine in cheese dry matter. Changes in concentration of total free amino acids during cheese ripening (0th, 30th, 60th, 90th and 120th day) were monitored. In water soluble extracts of cheese, the presence of free NH2 groups in all ripening stages was detected, which means smaller peptides and amino acids, whose concentration significantly (P<0.01) increased during ripening. Cheeses produced with and without microbial culture resulted in statistically significant differences (P<0.01) in content amino acids free on the 90th and 120th day of ripening. Cd - ninhydrin method was found to be suitable for cheese ripening monitoring, as well as for determination of the differences in mature characteristics of cheeses, depending on the production process.